What is love? An interpretation of love in Freudian and Lacanian psychoanalysis: Apakah cinta? Interpretasi cinta dalam psikoanalisis Freud dan Lacan - Muhammad Irfan Syaebani; Untung Yuwono; Embun Kenyowati Ekosiwi (Talenta Publisher, 2023)
GPS-based online dating sites make love becomes transactional. To examine this declaration, an analysis to interpret the meaning of love needs to perform. Sigmund Freud’s and Jacques Lacan’s psychoanalysis, pioneered analyzing love as an object of inquiry. This study analyzes the works of Freud and Lacan, which elaborate on love. The interpretation of love is required to put love in the proper context. According to Freudian and Lacanian psychoanalysis, love is merely a byproduct of drive or desire; thus, it implies that love is unconscious. Saying love has become meaningless is an exaggeration because we cannot place any ethical consideration on it since love is a primordial human instinct like hunger and thirst.